Smart Fire Detection System with Water Head Sprinkler - Rai, Praveen; Rai, Sudarshan; Sharma, Ranjana; Rai, Safal; Pradhan, Mausan; Hang Subba, Birendra; Kumar Sharma, Mukesh; Sherpa, Tenzing (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
It describes about the Smart fire detection system with water head sprinkler. The main aim of this project is a security system for the people to alert from fire disaster. The fire detection system saves many lives of people and also decrease the property losses. In this project we used Arduino Atmega328P and done a program for software. We used DHT11 temperature and gas sensor for detection of environmental changes. We also used buzzer to alert the people from the fire. For water sprinkler we used a 5v relay and dc water pump, relay is connected with dc water pump and pump will suck the water and extinguish through sprinkler head. Also, we used an LCD to display the alphabet image when the sensor senses the fire and smoke.
Keywords: Arduino atmega 328P; DHT11 temperature sensor; Gas sensor; Buzzer; DC water pump; LCD